2017
DOI: 10.1038/eye.2016.312
|View full text |Cite
|
Sign up to set email alerts
|

Nailfold capillary morphology in exfoliation syndrome

Abstract: Purpose The purpose of the study was to investigate nailfold microvascular morphology in exfoliation syndrome with or without glaucoma (XFS/XFG) compared with primary open-angle glaucoma (POAG) and control subjects using nailfold capillary videomicroscopy. Patients and methods We used a JH-1004 capillaroscope to perform nailfold capillary videomicroscopy on the fourth and fifth digit of the non-dominant hand. We enrolled 56 XFS/XFG patients, 87 POAG patients, and 75 control subjects. Masked observers graded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 51 publications
1
25
2
1
Order By: Relevance
“…The more frequent presence of nailfold hemorrhages in XFG, POAG and XFS in our study (44.4%, 41.3% and 57.1%) relative to normal controls (32.5%) is in line with the findings reported by Cousins et al [25], who speculated that impaired nitric oxide signaling might be responsible for nailfold hemorrhages. They supported this assertion by citing studies [46,47] whose authors demonstrated that asymmetric dimethyl arginine (ADMA), an inhibitor of nitric oxide synthase and contributor to endothelial cell dysfunction, is elevated in the aqueous humor and serum of XFS/XFG patients.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The more frequent presence of nailfold hemorrhages in XFG, POAG and XFS in our study (44.4%, 41.3% and 57.1%) relative to normal controls (32.5%) is in line with the findings reported by Cousins et al [25], who speculated that impaired nitric oxide signaling might be responsible for nailfold hemorrhages. They supported this assertion by citing studies [46,47] whose authors demonstrated that asymmetric dimethyl arginine (ADMA), an inhibitor of nitric oxide synthase and contributor to endothelial cell dysfunction, is elevated in the aqueous humor and serum of XFS/XFG patients.…”
Section: Discussionsupporting
confidence: 93%
“…Although the systemic vascular abnormalities in XFS and XFG have been extensively studied, according to an extensive literature search, there is a paucity of studies focusing on nailfold capillary morphology in patients with XFS and XFG [25], and their characteristics have never been compared as a part of a single investigation. In particular, to the best of our knowledge, this is the first attempt to investigate capillary morphology in patients with a newly diagnosed XFG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Кроме того, помимо органа зрения, ПЭС поражает множество других органов и тканей: кожу, соединительнотканные элементы висцеральных органов, базальные мембраны сосудов, гладкую и поперечнополосатую мышечную ткань, миокард [4,5]. Имеются данные о том, что ПЭС может быть ассоциирован с рядом экстраокулярных заболеваний, включая патологию сердечно-сосудистой системы, периферические капиллярные нарушения, сосудистую дисрегуляцию, а также нейродегенеративные заболевания, в частности болезнь Альцгеймера [6][7][8][9].…”
Section: Introductionunclassified